Assessment of the State of the Meat Market and the Reproductive Process in Terms of Ensuring Food Security - V. V. Vrublevskaya; A. I. Mamaeva (Статистика и экономика, 2022)
The reproduction process in agriculture is closely related to the agri-food market and ensuring the country’s food security. In modern literature, reproduction processes in agriculture are considered separately from the agri-food market, in turn, these concepts are interrelated. The development of the agri-food market and the level of food security set trends in the development of the reproduction process, and the conditions for the development of market relations, exports, imports and the current level of food security depend on the type of reproduction.The purpose of the study. The purpose of the study is to determine the type of reproduction process in the current situation on the meat market to assess the level of food security in Russia for meat products and to develop recommendations for the development of the meat market and the reproduction process in agriculture.Materials and methods. In this study, statistical methods were used to analyze reproduction and the situation on the meat market in terms of ensuring food security: descriptive statistics, comparative analysis, analysis of dynamic series. During the study, a method was used to determine the type of reproduction process, as well as a method for assessing the level of food security for meat products based on an assessment of supply and demand in the meat market. The data of official statistics at the federal and regional levels, as well as data from the reports of agricultural organizations, were used.Results. The presented methodology made it possible to determine the type of meat reproduction in the country, to assess the level of self-sufficiency and food security. The analysis of meat reproduction showed an expanded type. The average annual increase in meat production in natural units is about 5,0% over the period 2000-2020. The assessment of the availability of meat of own production showed an increase in the availability throughout the analyzed period and in 2020 reached the level of 100,1%. A decrease in dependence on imports (up to 5,8 %) and an increase in the share of exports (up to 5,4%) showed an optimal or sufficient level of food security (meat). Conclusion. According to the results of the study, the following conclusions can be drawn: there is an expanded type of reproduction process in Russia; the growth of meat production contributes to the self-sufficiency of the population with meat; there is an increase in demand for meat products on the market, a decrease in imports and an increase in the level of food security of the country. Further increase in the level of food security is possible while maintaining an expanded type of reproduction process. This will allow us to constantly increase the volume of meat production and increase the volume of meat exports to other countries, including China. The provision of high-quality and affordable food to the population of the country contributes to the optimization of the social climate in society, which in modern times in stressful conditions (pandemics, closed borders, military operations, etc.) is mandatory to suppress and smooth out stressful, panic food purchases in the future. Ensuring an adequate level of food security is also paramount, since the state of socio- political and military security depends on its level.